Frequency and Antibiotic Susceptibility of Bacteria Isolated in Patients with Blepharitis - Mahmood, Irum; Muhammad Shahid; Faisal Hanif; Muhammad Manzoor; Muhammad Awais; Muhammad Adnan (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency and antibiotic susceptibility of bacteria isolated in patients with blepharitis.StudyDesign: Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Oct 2019 to Oct 2021.Methdology: 160 cases of blepharitis, during a period of 2 years, who were not using topical or systemic antibiotics were recruited in this cross-sectional study. After detailed history and slit-lamp examination of eyelids and tears film each patient underwent sample collection under aseptic conditions, from the eyelid margin. The samples were inoculated in a culture of blood agar and chocolate agar (Biomeriux) , Then the susceptibility of the identified bacteria to common systemic and topical antibiotics were tested using the disc diffusion method (Rosco Neo-Sensitab). Results: In 160 patients,118(73.7%) were males and 42(26.3%) were females. According to type of blepharitis, 98(61.3%) had posterior blepharitis and 62(38.7%) had anterior blepharitis.Culture of eyelid sample of 77(48.1%) patients showed growth of coagulase-negative staphylococcus Coagulase-negative staphylococcus (CoNS) show greater resistance towards Penicillin 77(100%), Ciprofloxacin 55(72.5%) and Erythromycin 33(42.8%) however more susceptibility was shown towards Linezolid (CoNS). 71(45%) had Staphylococcus aureus isolated from their culture. 77(100%),Vancomycin 77(100%), Gentamycin 66(85.8%), Chloramphenicol 56(74.5%) and Cotrimoxazole 55(72.5%).Staphylococcus aureus show greater resistance towards Penicillin 72(100%),Ciprofloxacin 41(56.9%) and Tetracyclins 30(41.6%) however more susceptibility was found towards Gentamycin 72(100%), Linezolid 72(100%),Vancomycin 72(100%) and Chloramphenicol 61(84.7%). Conclusion: Coagulase-negative staphylococcus (CoNS) and Staphylococcus aureus have been the main isolated organisms in blepharitis. These bacteria have been shown to be resistant to Penicillin,